Effect of Use E- System Taxation and Understanding of the Internet on Personal Compliance of UMKM Personal Taxpayers - Tri Hardana, Anita Wijayanti & Yuli Chomsatu S (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to determine the effect of the use of e-system taxation and internetunderstanding of compliance with taxpayers of individuals UMKM. This researchwas conducted on Personal Taxpayer of UMKM registered on KPP PratamaSukoharjo. Sampling method using random sampling or randomly. The numberof respondents who participated in this study as many as 35 individual taxpayersUMKM registered in KPP Pratama Sukoharjo using e-system taxation.Techniques and methods of data analysis in use in this study by using multiplelinear regression analysis with the help of SPSS 22 program. The results of thisstudy indicate that the use of E-System Taxation and Internet Understandingaffect the compliance of individual taxpayers UMKM, it is evidenced in theANOVA model obtained Fcount of 8.016 with a significant level 0,000 andFtabel of 2.53. Because Fcount> Ftable (8.016> 2.53) then the independentvariable affected the compliance of individual taxpayers UMKMKeyword: e-system, e-filling, e-billing, e-SPT, Internet Understanding, TaxpayerCompliance UMKM